2023
DOI: 10.1007/s12194-023-00698-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of scattered radiation dose for radiological staff during portable chest examinations of COVID-19 patients

Abstract: The COVID-19 pandemic has resulted in a large increase in the number of patients admitted to hospitals. Radiological technologists (RTs) are often required to perform portable chest X-ray radiography on these patients. Normally, when performing a portable X-ray, radiation protection equipment is critical as it reduces the scatter radiation dose to hospital workers. However, during the pandemic, the use of a lead shield caused a heavy weight burden on workers who were responsible for a large number of patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The data collected were quantitatively analyzed to identify that the e-book can improve knowledge, recognition and practical skill for mammography machine QC. The percentage difference (%Diff) of the test's score between the control and experimental groups was calculated (Equation 1) (Moonkum et al, 2023). Students pair t-test statistics were calculated to determine a significant difference in comparing the use of e-book with the regular technique.…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…The data collected were quantitatively analyzed to identify that the e-book can improve knowledge, recognition and practical skill for mammography machine QC. The percentage difference (%Diff) of the test's score between the control and experimental groups was calculated (Equation 1) (Moonkum et al, 2023). Students pair t-test statistics were calculated to determine a significant difference in comparing the use of e-book with the regular technique.…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…X-ray tube voltage (kVp) and the patient thickness have position correlations for the ratio between intensities of scatter and incident radiation [1]. Nevertheless, it is an important radiation exposure dose issue to radiological staff in various radiological modalities including general and portable X-rays [2]. This issue received more concerns among interventional radiologists and cardiologists as the scatter radiation dose may cause adverse cataract events [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the irregularity of scatter radiation may reduce the effects of radiation dose reduction by increasing distance as pointed out by a recent study [6]. For the use of shielding, it has been commonly found that physical shielding has not been used in ward settings due to weight and mobility concerns [2]. Therefore, scatter radiation in portable X-rays may affect nearby patients significantly due to proximity to the exposed patient and lack of physical shielding.…”
Section: Introductionmentioning
confidence: 99%